Penerapan Model Pembelajaran Berbasis Pengalaman Dalam Meningkatkan Keterampilan Menulis Teks Laporan Hasil Observasi - Julfahnur, Julfahnur; Haliq, Abdul; Hapida, Hapida (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the improvement of observation report text writing skills of class X SMA Negeri 21 Makassar students by applying an experiential learning model. The type of research used in this study is Classroom Action Research consisting of two cycles. The research procedure includes, planning, action implementation, observation and reflection. The research sample was 36 students. Data collection consisted of observation sheets, and writing skill tests. The data analysis technique used descriptive quantitative. The results of the research at the pre-cycle stage were in the low category with an average score of 64 and learning completeness of only 17%. While at the cycle 1 stage it was in the medium category with an average score of 74 and learning completeness reached 53%. And in cycle 2 was in the high category with an average score of 84 and learning completeness reached 94% had met the KKM. Based on this, the application of experiential learning models in improving the skills of writing observation report texts can be concluded to have improved the skills of writing observation report texts and is very effective in the learning process.